The Role of Nurse Motivation, Competence And Workload for Increasing Completeness of Nursing Process Documentation At Class B Private Hospital In Jakarta - Monalisa, Irine; Hilmy, Mohamad Reza; Anindita, Rina (International Journal of Nursing and Health Services (IJNHS), 2023)
Background: Nursing care documentation is an important record both in electronic and manual in the form of a series of activities carried out by nurses in each process of nursing care. Objective: This study aims to examine the association between motivation, nurse competence and workload in increasing the completeness of the nursing care process documentation at Class B Private Hospitals in Jakarta. Method: This study used a cross-sectional method involving 109 nurses. The sampling technique used is purposive sampling. Data processing and hypothesis testing using multiple linear regression analysis method. Result: The results of this study found that motivation, competence, workload simultaneously increased the completeness of the documentation of the nursing care process. Workload plays a role in increasing the completeness of the nursing care process documentation at Class B Private X Hospital in Jakarta. Conclusion: Thus, hospital management can increase motivation, competence, and pay attention to workload, to improve the completeness of nursing care documentation. Recommendation: Managers could provide appreciation to nurses who carry out the nursing care process correctly, and could also periodically hold activities that encourage nurses to learn to think critically in solving a problem and expressing their ideas, and ensuring supervision goes well